Simulation-Assisted Design of Polycrystalline Zeolite Catalysts - Ding, Wenjin (KIT Scientific Publishing, 2016)
Zeolite membranes have shown promising applications in catalytic and separation processes in chemical industry. A simulation-assisted design method based on experiments and simulations is shown to guide the development of hierarchically structured catalyst systems based on zeolite membranes by predicting the optimal catalyst structure. A cornerstone of this method is a 3-D pore network model - crystallite-pore network model for simulation of diffusion and reaction in polycrystalline zeolites.